Restauración del bosque mediterráneo: aplicación de modelos de restauración a los encinares. - DE SIMÓN NAVARRETE, E.; Investigaci, Nnavarrete Centro D. E.; Apartado, Agraria D. E. Granada (II Congreso Forestal Español, 1997)
The activities in order to restore the mediterraneam forests have been constitued by the restoration of the structures and natural vegetation communities in order to preserve the water and soil in the drainage basins. A restoration of the vegetation covers in a drainage basin with hydrological and biological criteria have been projected, using sorne reforestation works in order to the best utilitation of the water resources and the conservation of the soil. The Quercus rotundifolia is one of the most extended species in the mediterranean area and it is apply for the forestation of the lands. This paper proposes a model of applied for its restoration. K.W.:
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Evolution; hydrological process; mediterranean forest; Restoration; structure